Preventing crime at assemblies - Madensen, Tamara (Public order policing, 2024)
In this chapter, assemblies are examined from a crime prevention perspective. We first discuss how crowds create crime opportunities. We then present three theories - routine activity theory, rational choice theory, and situational crime prevention - that can be used to explain crowd behaviors and develop crime interventions. The RDFC international model and 4D tactic, two assembly-focused crime prevention and training frameworks, are offered to help police improve safety and police - crowd interactions. We conclude with recommendations that will help police take immediate steps to better prevent and respond to crowd-related crime.